IL-27 suppresses spring viremia of carp virus replication in zebrafish. Issue 133 (February 2023) - Shi, Yanjie; Chen, Kangyong; Zhao, Xin; Lu, Yanan; Huang, Wenji; Guo, Jiahong; Ji, Ning; Jia, Zhao; Xiao, Hehe; Dang, Huifeng; Zou, Jun; Wang, Junya
Abstract: Interleukin (IL) 27 is a member of the IL-12 family and is a heterodimeric cytokine composed of IL-27A and Epstein-Barr virus-induced 3 (EBI3). It plays an important role in regulating inflammation and cancer progression. IL-27A not only functions by dimerizing with EBI3 but also acts alone. Here, we report that IL-27A and EBI3 suppress spring viremia of carp virus (SVCV) replication in zebrafish. Expression analysis reveals that il-27a and ebi3 were significantly upregulated in the ZF4 cells by SVCV and poly(I:C), and in the zebrafish caudal fin (ZFIN) cells overexpressed with SVCV genes. Interestingly, il-27a and ebi3 were not modulated by IFNφ1, indicating that they are not IFN stimulated genes (ISGs). Furthermore, overexpression of IL-27A and EBI3 alone inhibited SVCV replication in the EPC cells, but less potent than co-expression of IL-27A and EBI3. Intriguingly, IL-27A could not induce the expression of irf3, ifn, isg15 and mx1 . Taken together, our results demonstrate that IL-27A and EBI3 activate innate antiviral response in an IFN independent manner in zebrafish. Highlights: Zebrafish il-27a and ebi3 were induced by virus but not type I IFN. IL-27A did not upregulate irf3, ifn, isg15 and mx1. IL-27A and EBI3 inhibited replication of spring viremia of carp virus.